DEVELOPING EVALUATION INSTRUMENT FOR MATHEMATICS EDUCATIONAL SOFTWARE - Wahyu Setyaningrum (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2009)
The rapid increase and availability of mathematics software, either for classroom or individual learning activities, presents a challenge for teachers. It has been argued that many products are limited in quality. Some of the more commonly used software products have been criticized for poor content, activities which fail to address some learning issues, poor graphics presentation, inadequate documentation, and other technical problems. The challenge for schools is to ensure that the educational software used in classrooms is appropriate and effective in supporting intended outcomes and goals. This paper aimed to develop instrument for evaluating mathematics educational software in order to help teachers in selecting the appropriate software. The instrument considers the notion of educational including content, teaching and learning skill, interaction, and feedback and error correction; and technical aspects of educational software including design, clarity, assessment and documentation, cost and hardware and software interdependence. The instrument use a checklist approach, the easier and effective methods in assessing the quality of educational software, thus the user needs to put tick in each criteria. The criteria in this instrument are adapted and extended from standard evaluation instrument in several references. Keywords: mathematics educational software, educational aspect, technical aspect.